Biobehavioral Markers in Risk and Resilience Research - Harrist, Amanda W.; Gardner, Brandt C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This comprehensive reference explores the current and future state of biobehavioral markers in family resilience research, with special focus on linking biological and physiological measures to behavioral and health outcomes. It brings together the latest biobehavioral data on child-parent and couple relationships, adversity, and other key areas reflecting new technological advances in biobehavioral studies and translates these findings into implications for real-world practice and policy. The contributors' insights on biomarkers apply to emerging topics of interest (e.g., molecular genetics) as well as familiar ones (e.g., stress). Their interdisciplinary perspective helps to elaborate on risk and resilience factors for those creating the next generation of evidence-based interventions. Among the topics covered: • The immune system as a sensor and regulator of stress: implications in human development and disease • The psychobiology of family dynamics: bidirectional relationships with adrenocortical attunement • Intergenerational transmission of poverty: how low socioeconomic status impacts the neurobiology of two generations • The influence of teacher-child relationships on preschool children's cortisol levels • Challenges and strategies for integrating molecular genetics into behavioral science Besides its worth to researchers and practitioners studying and working with families at risk, Biobehavioral Markers in Risk and Resilience Research also has utility as a training text, offering a highly accessible presentation and discussion questions suited to classroom use.
The Immune System as a Sensor and Regulator of Stress: Implications in Human Development and Disease -- The Psychobiology of Family Dynamics: Bidirectional Relationships with Adrenocortical Attunement -- The Heart of Conversation: Using State-Space Grids to Disentangle Cardiovascular and Affect Dynamics During Couple Interaction. Intergenerational Transmission of Poverty: How Low Socioeconomic Status Impacts the Neurobiology of Two Generations -- The Influence of Teacher-Child Relationships on Preschool Children's Cortisol Levels -- Stress, Biomarkers and Resilience in Childhood and Adolescence: Advances in the Last Few Decades -- Challenges and Strategies for Integrating Molecular Genetics into Behavioral Science -- Risk as a First Derivative: Using Intensive Repeated Measures and Molecular Approaches to Studying Families.
Keywords: Sociology; Social groups; Developmental psychology; Public health; Sociology of Family, Youth and Aging; Developmental Psychology; Public Health